2021
DOI: 10.1111/jop.13149
|View full text |Cite
|
Sign up to set email alerts
|

An improved algorithm using a Health Canada‐approved DNA‐image cytometry system for non‐invasive screening of high‐grade oral lesions

Abstract: Background: DNA-image cytometry (DNA-ICM) is able to detect gross alterations of cellular DNA-content representing aneuploidy, a biomarker of malignancy. A Health Canada-approved DNA-ICM system, ClearCyte ® in combination with a cytopathologist's review, has demonstrated high sensitivity (89%) and specificity (97%) in identifying high-grade oral lesions. The study objective was to create an improved automated algorithm (iClearcyte) and test its robustness in differentiating high grade from benign reactive oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…It is unclear whether this additional cytological element may act as a confounding factor or provide additional predictive value. Recently published data, based on cytological samples, suggest it adds little and that diagnostic algorithms would be improved by omitting it (Parfenova, 2019;Parfenova et al, 2020). In most studies, DNA aneuploid status alone is used as the test result.…”
Section: Dna Aneuploidymentioning
confidence: 99%
“…It is unclear whether this additional cytological element may act as a confounding factor or provide additional predictive value. Recently published data, based on cytological samples, suggest it adds little and that diagnostic algorithms would be improved by omitting it (Parfenova, 2019;Parfenova et al, 2020). In most studies, DNA aneuploid status alone is used as the test result.…”
Section: Dna Aneuploidymentioning
confidence: 99%
“…Previous studies by our group in specialist clinic settings have shown DNA‐ICM to be more effective in detecting high‐grade dysplasia, cancers, or LGD at a high‐risk of progression 28,29 . This may explain the low sensitivity of DNA‐ICM in detecting LGD in our study.…”
Section: Discussionmentioning
confidence: 58%
“…27 Previous studies by our group in specialist clinic settings have shown DNA-ICM to be more effective in detecting high-grade dysplasia, cancers, or LGD at a high-risk of progression. 28,29 This may explain the low sensitivity of DNA-ICM in detecting LGD in our study. Thus, DNA-ICM may be more useful for detecting high grade dysplasia and high-risk LGDs that should be followed-up or treated following screening.…”
Section: Ta B L Ementioning
confidence: 67%
“…For molecular analysis, mass spectrometry [ 123 , 124 ] and DNA-image cytometry (DNA-ICM) [ 42 , 125 , 126 , 127 , 128 , 129 ] are utilized. DNA-ICM analysis can detect gross alterations of cellular DNA content representing aneuploidy [ 130 ]. Due to the lower cost and accessibility of brush biopsies, they are suitable to serve as a robust non-invasive automated oral cancer screening tool for mass screening to promote early oral cancer detection and decrease the number of unnecessary invasive biopsies.…”
Section: Resultsmentioning
confidence: 99%